Association of Blood Pressure With Stroke Risk, Stratified by Age and Stroke Type, in a Low-Income Population in China: A 27-Year Prospective Cohort Study - Du, Xin; Wang, Conglin; Ni, Jingxian; Gu, Hongfei; Liu, Jie; Pan, Jing; Tu, Jun; Wang, Jinghua; Yang, Qing; Ning, Xianjia (Frontiers in Neurology, 2019)
Association of stroke risk with new blood pressure criterion 2017 is unknown in China. We assessed the association between blood pressure (BP) values and stroke risk in a low-income population in Tianjin, China. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) values were categorized into five strata and strokes were recorded as stroke, ischemic stroke, and hemorrhagic stroke. Stroke risk was analyzed according to blood pressure stratum using Cox regression analysis. Overall, 4017 residents (age, ≥18 years) were included in this prospective cohort study. Over a 27-year follow-up period (total, 86,515.78 person-years), 638 participants experienced first-ever strokes. The stroke risk was higher among individuals with SBPs ≥140 mmHg or DBPs ≥90 mmHg than among those with SBPs <130 mmHg or DBPs <80 mmHg (reference group), after adjusting for covariates. However, hemorrhagic stroke risk increased only in participants with SBPs ≥160 mmHg. The stroke risk increased for individuals <65-years-old having BP values ≥130/80 mmHg and for individuals ≥65-years-old with BP values ≥160/90 mmHg. To reduce the stroke burden in China, target BP goals must be established for adults, with different targets for the middle-aged and the elderly segments of the population. These results are very important for guiding clinical practice and may be generalized to other developing countries experiencing rapid economic development and where transitions in the spectrum of prevalent diseases have occurred.